2021
DOI: 10.1021/acs.jpcc.1c04579
|View full text |Cite
|
Sign up to set email alerts
|

Nanotubular OMS-2 Supported Single-Atom Platinum Catalysts Highly Active for Benzene Oxidation

Abstract: The cryptomelane-type octahedral molecular sieve (OMS-2) exhibits excellent catalytic activity for the oxidation of volatile organic compounds (VOCs) due to its unique structure, and single-atom catalysts (SACs) have recently attracted much attention in heterogeneous catalysis. Herein, we adopted the hydrothermal redox reaction of KMnO4 and HCl aqueous solution at 120 °C for 12 h to first synthesize the nanotubular OMS-2 support and used the vitamin C and NaBH4 reduction methods to prepare the OMS-2-supported … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 52 publications
(90 reference statements)
0
17
0
Order By: Relevance
“…Based on the above discussion, it is concluded that the application of metal SACs for highly efficient oxidation of VOCs is still in its infancy and most catalysts studied have been oxide‐supported noble metals. To guide the future study of metal SACs in the catalytic oxidation of VOCs, we therefore provide our insights on this emerging research area below: (1) Several metal SACs have shown better activity than nanocatalysts in the oxidation of several VOCs, such as Ag 1 /HMO, [12a] Pt 1 /OMS‐2 [12b] and Pt 1 /meso‐Fe 2 O 3 [13] SACs in benzene oxidation and a Pt 1 /TiO 2 SAC in C 2 H 4 /C 3 H 6 oxidation [12e] . However, there are several cases showing that the specific activity of the metal SAC is less than that of the nanocluster and nanoparticle.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Based on the above discussion, it is concluded that the application of metal SACs for highly efficient oxidation of VOCs is still in its infancy and most catalysts studied have been oxide‐supported noble metals. To guide the future study of metal SACs in the catalytic oxidation of VOCs, we therefore provide our insights on this emerging research area below: (1) Several metal SACs have shown better activity than nanocatalysts in the oxidation of several VOCs, such as Ag 1 /HMO, [12a] Pt 1 /OMS‐2 [12b] and Pt 1 /meso‐Fe 2 O 3 [13] SACs in benzene oxidation and a Pt 1 /TiO 2 SAC in C 2 H 4 /C 3 H 6 oxidation [12e] . However, there are several cases showing that the specific activity of the metal SAC is less than that of the nanocluster and nanoparticle.…”
Section: Discussionmentioning
confidence: 99%
“…OMS‐2 supported precious metal SACs, such as Pt [12b,13] and Pd [14b] SACs, have also been reported in catalytic benzene oxidation. For example, a nanotubular OMS‐2 supported Pt SAC (0.0383 wt% Pt 1 /OMS‐2) exhibited better catalytic activity ( T 50 =166 °C and T 90 =189 °C) toward benzene as compared to a Pt nanocatalyst (0.09 wt% Pt NP /OMS‐2, T 50 =189 °C and T 90 =206 °C) in benzene oxidation [12b] . Moreover, the performance of the Pt 1 /OMS‐2 SAC was better than that of the other SACs (Table 1) in benzene oxidation.…”
Section: Application Of Single‐atom Catalysts For Vocs Abatementmentioning
confidence: 99%
See 3 more Smart Citations